Postoperative Nausea and Vomiting following Endoscopic Sinus Surgery under the Guidance of Adequacy of Anesthesia or Pupillometry with Intravenous Propofol/Remifentanil - Michał J. Stasiowski; Nikola Zmarzły; Beniamin Oskar Grabarek; Jakub Gąsiorek (MDPI AG, 2023)
Postoperative nausea and vomiting (PONV) constitutes an adverse event after endoscopic sinus surgery (ESS) under general anesthesia (GA) with intravenous opioids, such as remifentanil (RMF). Monitoring the nociception/antinociception balance using the surgical pleth index (SPI) or pupillary dilatation reflex (PRD) helps guide intravenous RMF infusion. We aimed to investigate whether their employment could help reduce the incidence of PONV in patients undergoing ESS. The data of 30 patients from the GA group, 31 from the SPI group, and 28 from the PRD group were analyzed. The initial RMF infusion rate of 0.25 µg/kg body weight/minute was increased by 50% when the SPI, PRD, or Boezaart Bleeding Scale (BBS) were elevated by >15, >5%, or >2 points, respectively, until they normalized. PONV was present in 7/89 patients (7.9%): 2/31 patients (6.5%) of the SPI group, 1/30 patients (3.3%) of the GA group, and 4/28 patients (14.3%) of the PRD group. Neither PRD nor SPI guidance for RMF administration reduced the incidence of PONV compared to standard practice. Further studies are required in order to investigate the possibility of PONV eradication in patients undergoing ESS under GA when it is possibly combined with paracetamol/metamizole preventive analgesia, as well as those using antiemetic prophylaxis based on the Apfel Score and premedication with midazolam.